STRATEGIC INNOVATION AND TECHNOLOGY INTEGRATION: A STUDY OF ENTREPRENEURIAL SUCCESS IN THE DIGITAL AGE: A LITERATURE REVIEW - Kartika Dinda Udhaty; Ritha F. Dalimunthe; Prihatin Lumbanraja (Cahaya Ilmu Bangsa, 2024)
This literature review explores the critical role of strategic innovation and technology integration in achieving entrepreneurial success in the digital age. In today's rapidly evolving business landscape, where technology plays a pivotal role in shaping market dynamics, understanding the intersection between innovation strategies and technological advancements is essential for entrepreneurs to thrive. The review examines various scholarly works, empirical studies, and theoretical frameworks to elucidate how strategic innovation and technology integration contribute to entrepreneurial success. Key themes analyzed include the importance of agile innovation processes, the adoption of disruptive technologies, the impact of digital transformation on business models, and the role of strategic leadership in driving innovation initiatives. Furthermore, the review highlights emerging trends and challenges faced by entrepreneurs in leveraging technology to innovate and compete effectively in the digital economy. By synthesizing existing literature, this review provides valuable insights for entrepreneurs, policymakers, and researchers seeking to navigate the complexities of entrepreneurship in the digital era and capitalize on opportunities for sustainable growth and success.